Translation Issues of Texts Related to the Political Sphere (Using Parallel Texts in English and Uzbek as Examples) - Botirova, Nilufar (The Lingua Spectrum, 2025)
This article provides an in-depth analysis of the theoretical, linguistic, cultural, and pragmatic issues related to the translation of political texts. Political texts are complex, multi-layered communicative units that not only convey information but also shape political awareness, mobilize audiences, and influence international public opinion. The article examines the approaches of prominent translation theorists such as M. Baker, L. Venuti, S. Bassnett, Z. Germans, and others regarding the translation of political texts. In particular, based on M. Baker’s “narrative” approach, the role of translation within social and ideological contexts is highlighted, and the challenges encountered in translating political texts are explored. The study mainly focuses on the key difficulties faced during the translation process from English into Uzbek. The theoretical foundations of the research rely on Nord’s (1997) classification of translation problems, which includes pragmatic, cultural, linguistic, and text-specific issues. The study also reviews scholarly literature on topics such as the concept of translation, translation approaches, specialized translation, translation challenges, the characteristics of political language, and the relationship between translation and political discourse. The research methodology is briefly outlined. The findings indicate that there is no single, fixed method for translating political texts, as translation is not merely a technical process but also requires a profound understanding of cultural, historical, and political contexts and their meanings.